Implication of attitude of graduate students in Oman towards entrepreneurship: An empirical study - Omer Ali Ibrahim; Sonal Devesh; Vaheed Ubaidullah (Journal of Global Entrepreneurship Research, 2017)
The purpose of the paper is to assess the implication of attitude of graduate students in Oman towards entrepreneurship. Exploratory factor analysis (EFA), and a multivariate regression model were used to assess the attitude and identify its influencing factors. Data was collected through a structured questionnaire, with a sample of 165 students, selected from four colleges in Muscat. Results show that although graduates in Oman have a positive attitude towards entrepreneurship, preference to start their own business after graduation is low. Increasing graduates' business knowledge and understanding of business risk, in addition to promoting entrepreneurship education can positively influence their attitude towards entrepreneurship. The government, higher education institutions and business incubators have an important role to play in changing the attitude of graduates towards entrepreneurship, and setting effective entrepreneurship strategies. Recommendations for future research have been made at the end of the paper.
Keywords: 650; Entrepreneurship; Attitude towards entrepreneurship; Exploratory factor analysis; Oman